Exploring home-based supportive and palliative care for men living with advanced-stage prostate cancer in a resource-limited Sub-Saharan African country (Ghana) - Salifu, Yakubu (2019)
Background The development of palliative care and research into palliative care are burgeoning fields in global south resource-poor countries. Due to inadequate institutional-based palliative care or health care institutions being stretched for resources, home-based care becomes an indispensable option. Home-based informal family caregiving is an under-explored area in Africa. In Ghana, PWAPC are mostly cared for in the home context. This study explored health care professionals, patients’ and caregivers’ experience of living with and or caring for PWAPC in a resource-poor setting where the bulk and responsibility for care is predominantly provided within the informal sector.